Design factors affecting harvesting losses of threshing unit of axial flow combine harvesters when harvest Thai Hom Mali rice - Chuan-udom, Somchai; Chinsuwan, Winit (Asia-Pacific Journal of Science and Technology, 2017)
The objective of this study was to study design factors affecting to harvesting losses of threshing unit of axial flow combine harvesters when harvest Thai Hom Mali rice. The results indicated that the increases of the rotor diameter (RD), the concave rod clearance (RC), the side concave clearance (SC), the number of peg tooth (NT), and the height of peg tooth (HT) decreased threshing unit losses, whereas the increase of the concave clearance (CC) and the upper concave clearance (UC) increased the loss.